Allograft recognition by recipient's natural killer cells: Molecular mechanisms and role in transplant rejection. (15th June 2021) - Hamada, Sarah; Dubois, Valérie; Koenig, Alice; Thaunat, Olivier
Abstract : The current transplant immunology dogma defends that allograft rejection is initiated by recipient's adaptive immune system. In this prevalent model, innate immune cells in general, and natural killer (NK) cells in particular, are merely considered as downstream effectors which participate in the destruction of the graft only upon recruitment by adaptive effectors: alloreactive T cells or donor‐specific antibodies (DSA). Challenging this vision, recent data demonstrated that recipients' NK cells are capable of a form of allorecognition because they can sense the absence of self HLA class I molecules on the surface of graft endothelial cells. Missing‐self triggers mTORC1‐dependent activation of NK cells, which in turn promote the development of graft microvascular inflammation and detrimentally impact graft survival. The fact that some patients develop chronic vascular rejection in absence of DSA or genetically‐predicted missing self suggests that other molecular mechanisms could underly NK cell allorecognition. This review provides an overview of these proven and putative molecular mechanisms and discusses future research directions in this emerging field in organ transplant immunology.